A Transcriptional Sequencing Analysis of Islet Stellate Cell and Pancreatic Stellate Cell. (24th January 2018) - Wang, Xiaohang; Li, Wei; Chen, Juan; Zhao, Sheng; Qiu, Shanhu; Yin, Han; Carvalho, Vladmir; Zhou, Yunting; Shi, Ruifeng; Hu, Jiannan; Li, Shenyi; Nijiati, Munire; et al.
Abstract : Background. Our previous studies have shown that islet stellate cell (ISC), similar to pancreatic stellate cell (PSC) in phenotype and biological characters, may be responsible for the islet fibrosis in type 2 diabetes. To further identify the differences between PSC and ISC and for better understanding of the physiological function of ISC, we employed genome-wide transcriptional analysis on the PSCs and ISCs of Wistar rats. Method. PSCs and ISCs from each rat were primarily cultured at the same condition. Genome-wide transcriptional sequence of stellate cells was generated. The identified differentially expressed genes were validated using RT-PCR. Results. 32 significant differentially expressed genes between PSCs and ISCs were identified. Moreover, collagen type 11a1 ( COL11A1 ), was found to be expressed 2.91-fold higher in ISCs compared with PSCs, indicating that COL11A1 might be a potential key gene modulating the differences between PSC and ISC. Conclusions. Our study identified and validated the differences between PSC and ISC in genome-wide transcriptional scale, confirming the assumption that ISC and PSC are similar other than identical. Moreover, our data might be instrumental for further investigation of ISC and islet fibrosis, and some differential expressed genes may provide an insight into new therapeutic targets for type 2 diabetes.